(untitled) (Modern education and development, 2025)
The study of stylistic characteristics in language provides valuable insights into how different linguistic systems convey meaning and express nuances. One of the most prominent and versatile stylistic devices in both English and Uzbek is comparison, which plays a crucial role in communication, literature, and everyday language. Comparison, whether explicit or implied, allows speakers and writers to highlight similarities and differences, drawing attention to qualities, actions, or ideas in a vivid and expressive manner.